2008
DOI: 10.1080/03630260701680276
|View full text |Cite
|
Sign up to set email alerts
|

Pyridoxal Isonicotinoyl Hydrazone (PIH) and its Analogs as Protectants Against Anthracycline-Induced Cardiotoxicity

Abstract: The risk of cardiotoxicity is the main drawback of anthracycline antibiotics. However, these drugs remain among the most effective and frequently used anti cancer drugs. In this study we aimed to assess the cardioprotective effects of aroylhydrazone iron (FE) chelators: pyridoxal isonicotinoyl hydrazone (PIH) and its two analogs: salicyladehyde isonicotinoyl hydrazone (SIH) and pyridoxal o-chlorbenzoyl hydrazone (o-108). In rabbits, chronic treatment with daunorubicin (DAU) (3 mg/kg weekly for 10 weeks) induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The ability of other iron chelating drugs, as we and others have shown [47][48][49], have produced mixed results in their ability to reduce anthracycline-induced cardiotoxicity. In the case of our study with ICRF-161, a dexrazoxane analog with three methylene linkers rather than two linkers, we showed that while the ICRF-161 hydrolysis product displaced Fe 3+ from its complex with doxorubicin, it did so much less effectively than for the dexrazoxane hydrolysis product.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of other iron chelating drugs, as we and others have shown [47][48][49], have produced mixed results in their ability to reduce anthracycline-induced cardiotoxicity. In the case of our study with ICRF-161, a dexrazoxane analog with three methylene linkers rather than two linkers, we showed that while the ICRF-161 hydrolysis product displaced Fe 3+ from its complex with doxorubicin, it did so much less effectively than for the dexrazoxane hydrolysis product.…”
Section: Discussionmentioning
confidence: 99%
“…We used a lipophilic iron chelator salicylaldehyde isonicotinoyl hydrazone (SIH), an analog of pyridoxal isonicotinoyl hydrazone that shows high affinity and selectivity for iron (Richardson and Ponka, 1998b). These chelators have been used in a number of in vivo and in vitro models, and the dosage we used was based on previous in vivo work (Richardson and Ponka, 1998a;Klimtova et al, 2003;Simunek et al, 2005Simunek et al, , 2008aSterba et al, 2005Sterba et al, , 2006Sterba et al, , 2007. An SIH solution was prepared as reported previously (Klimtova et al, 2003).…”
Section: Animals Cpmentioning
confidence: 99%
“…SIH and o-108 prevented both premature deaths of animals as well as significantly improved the DAU-induced impairment of cardiac function (LV EF, dP/dt max ), biomarkers of cardiac injury (cTnT), as well as histopathological parameters (255,256). However, dose escalation of all the aroylhydrazone chelators did not provide additional protection, but on the contrary, it hampered virtually all the beneficial effects of the chelators regarding both overall mortality rate and cardioprotection (244,255,256). Importantly, these higher chelators' doses were nontoxic and well tolerated when administered to animals alone.…”
mentioning
confidence: 98%
“…This has been observed despite the fact that the studied agents are even stronger and more selective intracellular iron chelators being able to displace iron from its complexes with ANTs, and their own complexes with this metal are less likely to redox cycle than those of ADR-925. Furthermore, in some of those studies, the cardioprotective dose range was quite narrow, and even a slight ( &2.5-fold) dose increase resulted in a disappearance of protective activity (244,255,256,282). It should be noted that while DEX is a prodrug that can be bioactivated to the chelating metabolite ADR-925 at the site of its effect, all the above-listed iron chelators are active ligands from the moment of administration.…”
mentioning
confidence: 99%
See 1 more Smart Citation